Growth of Merawangarab Chicken with Arab Chicken Backcross at Starter Periode - Nurcahya H; Detya Nuris Liarachma; Darwati S (Universitas Nasional Jakarta, 2023)
Indonesian native chickens have a high potency to be developed as egg produced chickens such as merawang and arab chicken. A study for genetic quality improvement through merawang and arab chicken crossing has been done and showed that their F1 results have a good heterosis effect. This research was conducted to observe the growth performance of merawangarab x arab and with a backcross breeding concept. The parameters of productivity measured were body weight, feed consumption, and feed conversion. Randomized complete block design used to analyzed the research. The average body weight of A-MA chicken were higher than the body weight of MA-A chicken. The result of statistical test were not significantly (P>0.05). A-MA chicken were more efficient in converting feed than MA-A chicken. Feed consumption and feed conversion between A-MA chicken and MA-A chicken were not significantly.